PENGARUH PENERAPAN METODE CONTEXTUAL TEACHING AND LEARNING DALAM PENGAJARAN KOSAKATA BAHASA INGGRIS SISWA KELAS XI DI SMA NEGERI 33 JAKARTA [THE EFFECT OF IMPLEMENTING CONTEXTUAL TEACHING AND LEARNING ON TEACHING ENGLISH VOCABULARY IN GRADE 11 AT SENIOR HIGH SCHOOL 33 JAKARTA] - Tito Dimas Atmawijaya (Universitas Pelita Harapan, 2018)
This study aimed at investigating the effect of vocabulary teaching in procedure texts using Contextual Teaching and Learning (CTL). The research was carried out with the English classes in the Social Sciences program which was taught vocabulary using the Contextual Teaching and Learning (CTL) method while another class used a traditional method in teaching vocabulary. The study used the quantitative data collected through the Post-Test after the treatment, questionnaires, and interviews. The data collected from the Post-Test were analyzed by implementing a t-test using SPSS 22 and counting average scores of both groups. The findings of the study indicate that teaching vocabulary using Contextual Teaching and Learning (CTL) method brings significant results. Furthermore, the results gathered from interviews and questionnaires confirmed that learners had a positive attitude towards CTL, as this method provided the students with a lot of activities which created a learning environment that was fun, enjoyable, and effective for improving the students’ vocabulary. Moreover, CTL also increased learners’ participation, scores, and collaboration.BAHASA INDONESIA ABSTRAK: Artikel jurnal ini membahas efek pengajaran kosakata bahasa Inggris teks prosedur dengan menggunakan metode Contextual Teaching and Learning (CTL). Penelitian ini dilakukan pada suatu kelas IPS yang menggunakan CTL, sedangkan kelas lain menggunaan metode pengajaran tradisional. Metode penelitian ini adalah kuantiatif dengan jenis Post-Test Only. Data penelitian diambil dengan menggunakan Post-Test yang diberikan sehari dan tiga minggu setelah perlakuan kepada kedua kelas partisipan. Analisis hasil penelitian dilakukan dengan menggunakan rerata dan uji t dependen dan independen menggunakan SPSS 22. Analisis tersebut menunjukkan peningkatan hasil yang signifikan pada kelas XI IPS 1 yang menerapkan metode CTL. Selain itu, hasil temuan penelitian dari wawancara dan kuesioner menunjukkan bahwa metode Contextual Teaching and Learning (CTL) memberikan pengaruh positif dalam pembelajaran kosakata di kelas, yaitu meningkatnya partisipasi pemelajar, kemampuan kosakata reseptif dan produktif, dan kolaborasi di antara pembelajar.